Strategi Pemasaran Online Dalam Merebut Konsumen, Studi Kasus Pengusaha Ritel Tradisional Di Kota Pekanbaru - Warman, Defi; Saib, Khaidir (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
Online marketing media with creative and educational displays containing comprehensive information about prices, promotions, product quality, and secure payment methods have captured consumer interest. However, not everyone is inclined to make purchases on online platforms due to distrust or uncertainty. Additionally, difficulties in online transactions and concerns about receiving incorrect orders contribute to consumer hesitancy. To continuously attract consumer interest in online shopping, online business practitioners are required to employ various effective and efficient online marketing (digital marketing) strategies. This applies not only to online entrepreneurs but also to traditional entrepreneurs in the city of Pekanbaru, Riau Province. Presently, numerous online product ordering applications offer various promotions and service conveniences to indulge consumers. With just a smartphone, consumers can conveniently order desired products to be delivered to their addresses and pay upon the arrival of the goods. This research analyzes the extent of the influence of online marketing on consumer decisions to purchase products in traditional retail stores in Pekanbaru, Riau Province. The conclusion of this research indicates that changes in marketing can be made in four aspects: product changes involve providing goods that meet the needs and arranging them in an orderly and attractive manner. Price changes include setting prices according to market affordability and offering price options. Promotion changes involve word-of-mouth promotions, advertising placements, discounts, and gifts. Service and facility changes include improvements in friendly and polite services, providing comfortable spaces, and offering credit purchase facilities